Performance and Stability of Lead Perovskite/TiO2, Polymer/PCBM, and Dye Sensitized Solar Cells at Light Intensities up to 70 Suns. (4th August 2014) - Law, Chunhung; Miseikis, Lukas; Dimitrov, Stiochko; Shakya‐Tuladhar, Pabitra; Li, Xiaoe; Barnes, Piers R. F.; Durrant, James; O'Regan, Brian C.
<x xml:space="preserve">Abstract</x> Three organic or hybrid photovoltaic technologies are compared with respect to performance and stability under the harsh regime of concentrated light. Although all three technologies show surprisingly high (and linear) photocurrents, and better than expected stability, no golden apples are awarded. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>